Perspektif Dakwah Tentang Cyberbullying - Mochammad Irfan Achfandhy; Fadhil Hardiansyah; Muhajir Muhajir; Umi Maisah (Postgraduate State Islamic Institute (IAIN) Metro, 2022)
Cyberbullying is a massive act of bullying in cyberspace in the digitalization era. However, da'wah as a social practice of empowering Islamic communities is still lacking in exploring cyberbullying. In response to this, this study aims to elaborate a da'wah study on cyberbullying through the film